High Hydrostatic Pressure–A Key Element to Investigate Molecular Dynamics in Biosystems - Peters, Judith (Frontiers in Physics, 2022)
Temperature variations are often used to investigate molecular dynamics through neutron scattering in biosystems, as the required techniques are well-known. Hydrostatic pressure is much less applied due to technological difficulties. However, within the last decade, a reliable and suitable equipment has been developed at the Institut Laue Langevin, Grenoble, France, which is now available on different instruments. Here, an overview on its application in relation with elastic incoherent neutron scattering to study, for instance, the impact of transitions on atomic mobility in biological samples, is presented, as well as the conclusions that can be drawn therefrom.